Growth, technology, and environmental change—nonlinearity and non-constant returns - Wei-Bin Zhang (Discrete Dynamics in Nature and Society)
This paper proposes a growth model with endogenous technology and environmental change. The economy consists of two sectors, production and environmental. The production sector produces goods with knowledge, labor, and capital as inputs under perfect competitive conditions. Knowledge accumulates through learning by doing. The environment is affected by production, consumption, the environmental sector's production efficiency, and the nature's purification. The simple model shows that it is difficult to explicitly judge the impact of factors such as environmental policy, knowledge accumulation efficiency and preference change on the environment.